Development of PHITS graphical user interface for simulation of positron emitting radioisotopes production in common biological materials during proton therapy. (28th March 2022) - Shahmohammadi Beni, Mehrdad; Yu, Kwan Ngok; Islam, M Rafiqul; Watabe, Hiroshi
Abstract: The Monte Carlo (MC) method is a powerful tool for modeling nuclear radiation interaction with matter. A variety of MC software packages has been developed, especially for applications in radiation therapy. Most widely used MC packages require users to write their own input scripts for their systems, which can be a time consuming and error prone process and requires extensive user experience. In the present work, we have developed a graphical user interface (GUI) bundled with a custom-made 3D OpenGL visualizer for PHITS MC package. The current version focuses on modeling proton induced positron emitting radioisotopes, which in turn can be used for verification of proton ranges in proton therapy. The developed GUI program does not require extensive user experience. The present open-source program is distributed under GPLv3 license that allows users to freely download, modify, recompile and redistribute the program.